Effective Assessment of Solutions to improve the quality of Teaching of Candidate art for Students (Training System) at People's Security Academy - Hai Ha, Ngo (International Journal of Humanities and Education Development (IJHED), 2022)
To improve the quality of teaching martial arts of the People's Police to students at the People's Security Academy. The topic used 05 routine research methods in sport and physical education to evaluate the effectiveness of solutions. The experimental subjects are 160 second and third-year students of 3 majors at the People's Security Academy, divided into 2 control and experimental groups, the experimental period is carried out in the academic year 2020-2021 from May September 2020 to July 2021. After experimenting with research methods in sports, the thesis has shown the effectiveness, superiority, and science of 09 solutions to improve the quality of martial arts teaching. People's Police for students at the People's Security Academy.